Occurrence of coronary artery disease in patients with type 2 diabetes mellitus can be predicted by neutrophil lymphocyte ratio - Bhuiyan, Mohammad Monzurul Alam; Islam, Md Saiful; Ferdousi, Sheuli; Borua, Dhiman; Ghosh, Mousumi; Akter, Sharmin; Jabed, Syed Md; Sultana, Tuhin; Ahmed, AN Nashimuddin (Bangladesh Medical Journal, 2016)
Neutrophil lymphocyte ratio (NLR) is the sign of balance between neutrophil & lymphocyte levels in the body and is an indicator of systemic inflammation. NLR is a new predictor for cardiovascular risk and mortality and by which occurrence of coronary artery disease can be predicted in type 2 DM patients. This case control study was conducted in the Department of Clinical pathology in collaboration with Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2014 to February 2015 to assess the NLR as a useful predictive marker for coronary artery disease in type 2 DM patients detected by coronary angiography. Total 134 patients waiting for coronary angiography in the Department of Cardiology, BSMMU were enrolled in this study. Among them, 84 patients were considered as Group A (DM with CAD). All of them had ? 50% coronary artery stenosis on coronary angiography. Fifty patients with DM but without CAD were enrolled in Group B and considered as controls. Statistically significant increased NLR was found in Group A (type 2 DM patients with CAD) compared to Group B (type 2 DM patients without CAD). So, NLR can be used to predict adverse outcome i.e. coronary artery disease in patients with type 2 DM. Bangladesh Med J. 2015 Sep; 44 (3): 130-135